The Effect of Gold Price and Integrated Marketing Communication: Determinants of Interest in Gold Installment Financing at BSI - Riris Tri Maulida; Tri Pujiati; Taufiqur Rahman (Jesya, 2026)
This research explores how the price of gold and Integrated Marketing Communication (IMC) influence customer interest in gold installment financing at PT Bank Syariah Indonesia (BSI). Gold installment financing serves as a Sharia-compliant investment option based on a murabahah contract, allowing customers to gradually obtain gold through fixed installment payments. The rising demand for gold as a safe haven asset underscores the significance of both economic and marketing elements in shaping customer choices. This study utilizes a quantitative explanatory approach and employs multiple linear regression analysis. Data were gathered via structured questionnaires distributed among BSI customers and were examined through validity and reliability assessments, classical assumption tests, and hypothesis testing methods. The results indicate that gold price and IMC positively and significantly affect customer interest. Moreover, IMC demonstrates a more dominant influence compared to gold price, indicating that effective and integrated marketing communication strategies play a critical role in enhancing customer awareness, trust, and understanding of gold installment products. These results suggest that while gold price reflects rational economic considerations, IMC functions as a strategic communication mechanism that strengthens customers’ behavioral intentions. This study provides theoretical contributions by integrating economic and marketing determinants within a single analytical framework and offers practical implications for Islamic banking institutions in developing adaptive pricing policies and more effective communication strategies to increase customer interest in gold installment financing.